A study of current practices for avoiding and resolving trade dispute in the wood-based manufacturing industries in Sarawak : the industrial relations perspective - Jack Meredu, Anak Ko (Faculty of Social Sciences, 2003)
The present study investigates the causes of industrial disputes in the wood-based manufacturing industries in Sarawak, and examines how conflict-avoiding strategies (CAS) employed by the management can reduce these conflicts.